EFEKTIFITAS KONSUMSI AIR TEBU KOMBINASI DENGAN AIR JAHE TERHADAP HIPEREMESIS GRAVIDARUM DI WILAYAH KERJA PUSKESMAS RAWAT INAP SIDOMULYO PEKANBARU - Rahayu Kusuma Wardani (Jurnal Ilmu Kebidanan, 2020)
Hyperemesis Gravidarum Is a excessive navsea in pregnant woman it disturb the daily activity of the women. Cane and ginger are the nause. Cane contains glucose that can reduce acid emphasis. Ginger constans gingerol that ccin smooth the blood. The aim of this research is to know Effectiveness Consumes Water Of The Can Cambinated With Water Of Ginger Against Hiperemesis Gravidarum In the Puskesmas area Rawat Inap Sidomulyo Pekanbaru. Design of this research is used quasy eksperimen with design one grup pretest and posttest. Sample of the research is pregnant women who liave hyperemesis gravidarum level 1 there are 15 respondences for inetervensi. The time of the research conducted in December 2017 until April 2018. Data collection on this research is used obervation sheet. The data analysis is used T Dependent test. Result of this research show us that the water of cane cambination with the water of ginger in reduce the nausea in the women pregnant in the Puskesmas area Rawat Inap Sidomulyo Pekanbaru with the value p-value (α=0.05). Recomended nausea one of them is consume water of cane combination with water of ginger to reduce the use of nonfarmakologi’s drugs.